Impact of hormonal crosstalk on plant resistance and fitness under multi-attacker conditions - Vos, Irene A.; Moritz, Liselotte; Pieterse, Corné M. J.; Van Wees, Saskia C. M. (Frontiers in Plant Science, 2015)
The hormone salicylic acid (SA) generally induces plant defenses against biotrophic pathogens. Jasmonic acid and its oxylipin derivatives (JAs) together with ethylene (ET) are generally important hormonal regulators of induced plant defenses against necrotrophic pathogens, whereas JAs together with abscisic acid (ABA) are implicated in induced plant defenses against herbivorous insects. Hormonal crosstalk between the different plant defense pathways has often been hypothesized to be a cost-saving strategy that has evolved as a means of the plant to reduce allocation costs by repression of unnecessary defenses, thereby minimizing trade-offs between plant defense and growth. However, proof for this hypothesis has not been demonstrated yet. In this study the impact of defense hormonal crosstalk on disease resistance and fitness of Arabidopsis thaliana when under multi-species attack was investigated. Induction of SA- or JA/ABA-dependent defense responses by the biotrophic pathogen Hyaloperonospora arabidopsidis or the herbivorous insect Pieris rapae, respectively, was shown to reduce the level of induced JA/ET-dependent defense against subsequent infection with the necrotrophic pathogen Botrytis cinerea. However, despite the enhanced susceptibility to this second attacker, no additional long-term negative effects were observed on plant fitness when plants had been challenged by multiple attackers. Similarly, when plants were grown in dense competition stands to enlarge fitness effects of induced defenses, treatment with a combination of SA and MeJA did not cause additional negative effects on plant fitness in comparison to the single MeJA treatment. Together, these data support the notion that defense hormonal crosstalk in plants during multi-attacker interactions allows plants to prioritize their defenses, while limiting the fitness costs associated with induction of defenses.